Harnessing 3D cell models and high-resolution imaging to unveil the mechanisms of nanoparticle-mediated drug delivery - Chalkley, Alannah S.; Lopez, Maëva T.; Mysior, Margaritha M.; Brink, Madeleen C.; Kelly, Suainibhe; Simpson, Jeremy C. (Frontiers in Bioengineering and Biotechnology, 2025)
Nanoparticles and nanosized materials offer huge potential in the field of drug delivery. One key aspect that dictates their successful development is the need to understand how they interact with cells at both the macro and molecular level. Delineating such interactions is vital if nanomaterials are to be targeted not only to particular organs and tissues, but also to individual cell types and ultimately specific subcellular locations. In this regard, the development of appropriate in vitro cell models is an essential prerequisite before animal and human trials. In recent years, as the methodology for their growth has been refined, there has been a huge expansion in the use of pre-clinical 3D cell culture models, particularly spheroids and organoids. These models are attractive because they can be combined with high-resolution fluorescence imaging to provide real-time information on how nanomaterials interact with cells. Confocal fluorescence microscopy and its associated modalities, along with high-content screening and analysis, are powerful techniques that allow researchers the possibility of extracting spatial and temporal information at multiple levels from cells and entire 3D assemblies. In this review, we summarise the state of this field, paying particular emphasis to how imaging of such models is now beginning to provide rich quantitative data about nanomaterial entry and trafficking in cells growing in 3D. We also offer a perspective on the challenges faced by such approaches, and the important questions that the drug delivery field still needs to address.